Resilience as resistance to the new managerialism: portraits that reframe nursing through quotes from the field. (3rd February 2015) - Cope, Vicki; Jones, Bronwyn; Hendricks, Joyce
Abstract : Aim: This paper acknowledges the relationship between resilience and the new managerialism of contemporary nursing. Methods: Qualitative portraiture methodology. Discussion: The new managerialism in hospital settings results in a rapidly increasing turnover of acutely ill or comorbid patients, which directly relates to retention and quality service. In education settings, the management imperative to recruit more students into the profession combined with financial cutbacks leads to similar tensions. In aged care the trend equates care directly with funding, with the same effect. Yet despite this, many registered nurses remain working. Portraiture explored 'why' nurses remain in workplaces often described as awful. The resilience of nurses is seen through their stories and reframed to highlight resilience as a form of resistance to the new managerialism inherent in contemporary healthcare. Conclusion: This paper describes some of the hallmarks of new managerialism where workforce pressures force practices that do not value the 'human resource'. Implications for nursing management: The quotes from the field give insight into the nurse's world view and have implications for managers, educators and employers, as well as for consumers of nursing care.